Biscuit meets the neighbors - Capucilli, Alyssa Satin, 1957-; Schories, Pat ([New York] : HarperFestival, 2002)
Biscuit, Daisy, and their owner greet their new neighbors with a basket of treats.
Board pages.
Cover title.
Keywords: Animals -- Infancy -- Fiction; Biscuit (Fictitious character) -- Fiction; Dogs -- Fiction; Moving, Household -- Fiction; Neighbors -- Fiction